(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2024)
This paper discusses the importance of the development of skills associated with historical thinking and the use of narratives for learning history. The aim of the research was to investigate the students’ perceptions regarding the use of historical narrative productions for learning and the incidence of these on the conceptions of historical knowledge. For this purpose, a case study was chosen, carrying out a descriptive analysis and content analysis. The instruments used were a semi-structured questionnaire and the students’ productions. The participants consisted of a group of 19 students in the 4th year of ESO for the subject of Geography and History. The analysis and the results of the case study show a positive evaluation of the students regarding the use of narratives and a development of the conceptions on historical knowledge.